Impact of external openness on the specialization of Peruvian fruit and vegetable exports (LACCEI, 2024)
Trade opening policies are part of the economic development and relative performance for the productive sectors of a nation, so this research aims to establish the impact of external openness in the specialization of Peruvian fruit and vegetable exports, under theoretical foundations of role of the State in the growth of agricultural exports and growth based on exports of fruits and vegetables. All under the descriptive and quantitative methodologies reinforced with econometric models from the review of statistical sources. Among the main results was that the fruit export sector grows at annual rates of 18% while that of vegetables at 15% and that Peru's trade liberalization policies have positively affected the specialization of these sectors. In this sense, part of the specialization of the fruit and vegetable sector is due to the commercial opening strategy of the Peruvian State.